(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Saliva is essential for maintaining healthy oral tissues and teeth, as well as for proper oral function, by consistently lubricating and protecting the mucosal surfaces. Salivary gland dysfunction refers to conditions that result in reduced saliva production (hypofunction), excessive saliva flow (sialorrhea or hypersalivation), or alterations in saliva composition. Xerostomia, the subjective sensation of dry mouth, is frequently linked to salivary gland hypofunction and can significantly impact nutrition, social interactions, and overall quality of life. Various local or systemic disorders are common causes of impaired saliva secretion. Some of these issues relate directly to gland pathology or the host’s underlying conditions, while others may involve nerve damage to the glands or be caused by medical treatments, such as radiation therapy for head and neck cancers or medication side effects. Many patients with conditions affecting salivary function often receive treatments that can further reduce saliva production or lead to xerostomia as a side effect. Consequently, it can be challenging to determine whether symptoms are due to the underlying disease or the treatment itself. Therefore, a comprehensive diagnostic evaluation and timely identification of salivary gland dysfunction are essential for delivering appropriate, evidence-based interventions to prevent oral complications and to implement personalized management strategies for xerostomia.